2022
DOI: 10.3389/fanim.2022.834634
|View full text |Cite
|
Sign up to set email alerts
|

Passive, Active, and Proactive Systems and Machines for the Protection and Preservation of Animals and Animal Species

Abstract: Digitalization and automation are expanding into many areas, resulting in more widespread use of partially and fully autonomous machines and robots. At the same time, environmental and other crises and disasters are on the rise, the world population is growing, and animals are losing their habitat. Increasingly, machines and robots such as agricultural vehicles, autonomous cars, robotic lawnmowers, or social robots are encountering animals of all kinds. In the process, the latter are injured or killed. Some ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Additionally, the ‘interactive’ bioinspired robots ( Datteri, 2020 ) can potentially be used to train captive animals before their reintroduction into their natural habitats. Moreover, these robots can mitigate human-wildlife conflicts, such as using robot wolves instead of electric fences to safeguard agricultural fields from wildlife ( Bendel, 2022 ), or utilizing bird-inspired flapping robots to deter birds from congregating near airports during flight operations ( Patel and Rughani, 2022 ). Bioinspired robots can also be used to non-invasively study animal behavior and locomotion in the wild ( Datteri, 2020 ; Romano et al, 2020 ; Li et al, 2022 ), as shown in studies on bat echolocation ( Bou Mansour et al, 2019 ) and locust jumping direction ( Romano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ‘interactive’ bioinspired robots ( Datteri, 2020 ) can potentially be used to train captive animals before their reintroduction into their natural habitats. Moreover, these robots can mitigate human-wildlife conflicts, such as using robot wolves instead of electric fences to safeguard agricultural fields from wildlife ( Bendel, 2022 ), or utilizing bird-inspired flapping robots to deter birds from congregating near airports during flight operations ( Patel and Rughani, 2022 ). Bioinspired robots can also be used to non-invasively study animal behavior and locomotion in the wild ( Datteri, 2020 ; Romano et al, 2020 ; Li et al, 2022 ), as shown in studies on bat echolocation ( Bou Mansour et al, 2019 ) and locust jumping direction ( Romano et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%